Peningkatan Kesadaran Hukum Penggunaan Hak Pilih Pemilih Pemula di MA DDI Padanglampe - Farah Syah Rezah; Andi Tenri Sapada; Sri Amlinawaty A. Muin (Universitas Pahlawan Tuanku Tambusai, 2023)
The activity of community dedication which is done at MA DDI Padanglampe was to increase the legal awareness the use of suffrage for novice voters by using need assestment method, legal counselling, accompaniment and evaluation for the students of MA DDI Padanglampe. The purpose of this activity is to make the students understand their important role in the election. Therefore, the activity of legal counselling and accompaniment were programmed for the students of MA DDI Padanglampe and the results were; they are capable to determine which categories are included as novice voters; ready to objectively evaluate the nominating figures; and realize the importance of using suffrage in election.